Periodontal Status and Gingival Conditions of the Tea Workers (Eastern Medical College Journal, 2022)
Background: Periodontitis and gingivitis are prevalent chronic inflammatory diseases. The examination of the periodontal and gingival conditions is complex and requires a proficient dental healthcare provider to detect the patient’s definite problems.Methodology: The study was designed as a cross-sectional study to assess the periodontal status and gingival conditions of the 372 tea workers in the purposively selected Premnagar tea garden located in Moulvibazar district, Sylhet 3200, Bangladesh. ‘Community Periodontal Index’ (CPI) was used to measure the periodontal status.Results: Most of the workers (38.2%) were from the age group ≥37 years and illiterates (62.1%). More than two-fourths (57.8%) had detected calculus during probing, one-fourth (25.3%) had a shallow pocket and only 11.6% had healthy periodontal status. The prevalence of poor periodontal status was 88.4%. Among the dental cleaning aids such as toothbrush users, 15.6% had healthy periodontal status, whereas the smokeless tobacco non-users (22.6%) and pan-supari non-chewers (75.0%) had healthy periodontal conditions. The level of periodontal status factors was statistically significant with age, educational qualification, and monthly household income (p